2021
DOI: 10.31219/osf.io/zxmun
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gene therapy may benefit inherited ichthyoses with concurrent fungal infections and severe ich thyroidoses

Abstract: Despite the fact that inherited ichthyoses with simultaneous fungal infections have been documented for more than 50 years, the connection between the two remains unknown. Because ichthyosis makes it harder to identify a concurrent fungal infection, it's important to pay close attention to prevent missing or delaying a diagnosis. The underlying ichthyosis makes treating fungal infections more difficult, and severe and recurrent infections need further attention. Those with severe ichthyoses may benefit from ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…Another research found a link between CRP and fibrinogen and an increased risk of mortality in COPD patients (88). Fibrinogen is an acute phase protein (340 kDa homodimeric glycoprotein) that is largely generated in hepatocytes and circulates at a concentration of 2-5 mg/mL in healthy people (89). The most promising COPD measure is plasma fibrinogen, which is the only FDA-approved blood-based drug development biomarker for patients with a high mortality risk (90).…”
Section: Other Biomarkers For Copdmentioning
confidence: 99%
“…Another research found a link between CRP and fibrinogen and an increased risk of mortality in COPD patients (88). Fibrinogen is an acute phase protein (340 kDa homodimeric glycoprotein) that is largely generated in hepatocytes and circulates at a concentration of 2-5 mg/mL in healthy people (89). The most promising COPD measure is plasma fibrinogen, which is the only FDA-approved blood-based drug development biomarker for patients with a high mortality risk (90).…”
Section: Other Biomarkers For Copdmentioning
confidence: 99%
“…Li et al also achieved allele-specific gene editing in the retinas of Rho-P23H knock-in mice (88), which targeted the P23H allele with a single-nucleotide alteration. Shinmyo et al also used in utero electroporation to transfer a plasmid containing CRISPR/Cas components into the mouse brain for successful brain-specific gene editing in vivo (89). These studies proved the viability of CRISPR/Cas9 delivery through DNA in vivo.…”
Section: Crispr/cas Gene Editing and Delivery Without The Use Of Virusesmentioning
confidence: 99%
“…Interferons (IFNs) are another well-known cytokine used in cancer treatment. IFNs are a protein and glycoprotein family having antiviral, antiproliferative, and immunomodulatory properties (89). IFNs are categorised according to their capacity to bind to certain receptors.…”
Section: In Cancer Immunotherapy Cytokines Play An Important Rolementioning
confidence: 99%